SELECTION OF SOCIAL CHANNELS OF COMMUNICATION ON THE EXAMPLE OF AN AGRICULTURAL COMPANY - Nedeljković, Miroslav; Krstić , Svetozar; Rakić , Sveto (Economics of Agriculture, 2025)
The paper selected the most efficient social communication channel in an agricultural enterprise. On this occasion, an innovative expert decision-making method was used, namely its fuzzy variant SiWeC and RAWEC. Ten criteria and six alternatives were set, and the results show that the criteria “Number of users”, “User characteristics” and “Feedback speed” have the greatest importance, while the most important (most favorable) social channel of communication is “facebook.”The successful application of the method used was confirmed, as well as the importance of certain factors in the form of analyzed criteria, the number of which should be increased in future research, and the method itself should be further developed.